A Screen for F1 Hybrid Male Rescue Reveals No Major-Effect Hybrid Lethality Loci in the Drosophila melanogaster Autosomal Genome. - Cuykendall, T.N.; Satyaki, P.; Ji, S.; Clay, D.M.; Edelman, N.B.; Kimchy, A.; Li, L.H.; Nuzzo, E.A.; Parekh, N.; Park, S.; Barbash, D.A. (G3 : genes - genomes - genetics, 2014)
Hybrid sons between Drosophila melanogaster females and D. simulans males die as 3rd instar larvae. Two genes, D. melanogaster Hybrid male rescue (Hmr) on the X chromosome, and D. simulans Lethal hybrid rescue (Lhr) on chromosome II, interact to cause this lethality. Loss-of-function mutations in either gene suppress lethality, but several pieces of evidence suggest that additional factors are required for hybrid lethality. Here we screen the D. melanogaster autosomal genome by using the Bloomington Stock Center Deficiency kit to search for additional regions that can rescue hybrid male lethality. Our screen is designed to identify putative hybrid incompatibility (HI) genes similar to Hmr and Lhr which, when removed, are dominant suppressors of lethality. After screening 89% of the autosomal genome, we found no regions that rescue males to the adult stage. We did, however, identify several regions that rescue up to 13% of males to the pharate adult stage. This weak rescue suggests the presence of multiple minor-effect HI loci, but we were unable to map these loci to high resolution, presumably because weak rescue can be masked by genetic background effects. We attempted to test one candidate, the dosage compensation gene male specific lethal-3 (msl-3), by using RNA interference with short hairpin microRNA constructs targeted specifically against D. simulans msl-3 but failed to achieve knockdown, in part due to off-target effects. We conclude that the D. melanogaster autosomal genome likely does not contain additional major-effect HI loci. We also show that Hmr is insufficient to fully account for the lethality associated with the D. melanogaster X chromosome, suggesting that additional X-linked genes contribute to hybrid lethality.